The Initial Vascular Access Type Contributes to Inflammation in Incident Hemodialysis Patients - Mala Sachdeva; Adriana Hung; Oleksandr Kovalchuk; Markus Bitzer; Michele H. Mokrzycki (International Journal of Nephrology)
Background. The contribution of the hemodialysis (HD) vascular access type to inflammation is unclear. Methods. We conducted a prospective observational study in an incident HD population. C-reactive protein (CRP), interleukin-6 (IL-6), and interferon-γ-induced protein (IP-10) were measured before and at 6-time points after access placement for 1 year. Results. Sixty-four incident HD patients were included (tunneled catheter (TC), 𝑛=40, arteriovenous fistula (AVF), 𝑛=14, and arteriovenous graft (AVG), 𝑛=10). A mixed effects model was performed to adjust for age, sex, race, coronary artery disease, diabetes mellitus, infections, access thrombosis, initiation of HD, and days after access surgery. In comparison to AVFs, the presence of a TC was associated with significantly higher levels of CRP (𝑃=0.03), IL-6 (𝑃=0.07), and IP-10 (𝑃=0.03). The presence of an AVG was associated with increases in CRP (𝑃=0.01) and IP-10 (𝑃=0.07). Conclusions. Patients who initiate HD with a TC or an AVG have a heightened state of inflammation, which may contribute to the excess 90-day mortality after HD initiation.